Tetrabutyl-tetraphenyl-diindenoperylene derivatives as alternative green donor in bulk heterojunction organic solar cells - Meiss, J; Hummert, M; Petrich, A; Pfuetzner, S; Leo, K; Riede, M (Elsevier, 2011)
We present the material 2,3,10,11-tetrabutyl-1,4,9,12-tetraphenyl- diindeno[1,2,3-cd:1′,2′,3′-lm] perylene (Bu4-Ph4-DIP) as alternative green donor for bulk heterojunction small molecule organic solar cells (SMOSC). It is shown that Bu4-Ph4-DIP exhibits suitable absorption characteristics to be a potential material to fill the absorption gap between the commonly used standard absorbers ZnPc and C60. Devices with bulk heterojunctions of Bu4-Ph4-DIP:C60 display very high open circuit voltages of 0.99 V, high fill factors of up to 57%, and experiments yield promising efficiencies of η>2%. Such green-blue absorbing SMOSC are characterized by current voltage and external quantum efficiency measurements, and material properties are studied. It is shown that the devices are responsive to substrate heating, and that different donoracceptor mixing ratios can increase device performance. Possible influences of mixing ratio and heating on device morphology and electrical properties are discussed.